Tyrimas aptaria: negyvas subjektas + aktyvų veiksmą reiškiantis veiksmažodis angliškame lingvistiniame diskurse - Šeškauskienė, Inesa (Kalbotyra, 2009)
The present paper discusses the ‘inanimate subject + active verb’  pattern in research papers in applied linguistics attempting to identify major differences between linguistic discourse as a discourse of human sciences and hard sciences (as represented in Master 2001) and account for the usage and meaning of the pattern under investigation in the framework of the CTM.  The quantitative aspect of the investigation includes the overall frequency count of the pattern in the corpus and their distribution per 1000 words as well as the count of inanimate subjects and active verbs according to frequency, their semantic properties and functions. There is a comparative dimension involved in the investigation: the results of the present investigation into linguistic discourse roughly representing human sciences is compared to Master’s investigation into ‘hard’ sciences (2001). The tendency to use the pattern in the explanatory environment has been confirmed. The qualitative aspect of the analysis involves the interpretation of the results in the framework of conceptual theory of metaphor (CTM). The interpretation of the results in the framework of the CTM has yielded several major metaphorical extensions: research as a person, research as a journey, research as construction/building, research as economic activity, research as (uncovering) a secret.  The personification type of metaphor (research as a person) seems to overlap with what is usually interpreted as metonymy.  This research has some implications for teaching academic English to non-native speakers of English, especially speakers of languages which do not have any such patterns.